2020
DOI: 10.3390/su12219090
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Top Management’s Support on the Collaboration of Green Supply Chain Participants and Environmental Performance

Abstract: The purpose of this study is to determine whether the support of top management significantly improves the level of environmental collaboration with participating companies upstream and downstream of the green supply chain and the impact on environmental performance. The results of the empirical analysis of 301 companies that are establishing a green supply chain are as follows. First, top management’s support positively affects the level of collaboration with suppliers and customers in the green supply chain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Furthermore, manufacturing companies achieve strategic sourcing that is implemented well [37]. The SC partnership that the company builds in the form of supplierbuyer collaboration can increase trust and ease of fulfilling product requirements [23,25]. The measures used for SC partnerships in the pandemic era are extra coordination with partners during a pandemic (SCP.1), on-time delivery of materials from suppliers (SCP.2), suppliers understanding order changes during a pandemic (SCP.3), suppliers' collaboration in helping companies during a pandemic (SCP.4), and coordinate activities with suppliers during the pandemic (SCP.5).…”
Section: Supply Chain (Sc) Partnershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, manufacturing companies achieve strategic sourcing that is implemented well [37]. The SC partnership that the company builds in the form of supplierbuyer collaboration can increase trust and ease of fulfilling product requirements [23,25]. The measures used for SC partnerships in the pandemic era are extra coordination with partners during a pandemic (SCP.1), on-time delivery of materials from suppliers (SCP.2), suppliers understanding order changes during a pandemic (SCP.3), suppliers' collaboration in helping companies during a pandemic (SCP.4), and coordinate activities with suppliers during the pandemic (SCP.5).…”
Section: Supply Chain (Sc) Partnershipmentioning
confidence: 99%
“…The supplier-buyer relationship enhances collaboration and improves organization agility [23]. The strategic partnership with external partners impacts the company's operational performance and competitive advantage [24][25][26]. The implementation of SC agility requires managers to know when to invest in resources, how much to invest, and where to invest in the supply chain flow to achieve improved performance [27].…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhou et al (2018), interorganizational collaboration is crucial to SC flexibility, allowing an organization to rapidly minimize response time and generate diverse product combinations swiftly and economically (Zhou et al , 2018). Moreover, supplier–buyer collaboration boosts SC agility, further enhancing operational performance and competitive advantages (Lee and Joo, 2020). In particular, responsiveness is of significant importance to businesses as it enables them to meet the demands of global customers effectively and enhance overall SC responsiveness (Thongrawd et al , 2020; Asamoah et al , 2021; Nenavani and Jain, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Burki et al (2019) [51] examined the relationship between top management commitment and process innovation in the green supply chain (GSC), in the form of green process innovation and green managerial innovation in selected ISO 14000 certified Turkish exporting firms located in the Izmir region (Turkey). Meanwhile, Lee and Joo (2020) [52] investigated whether support from top management can significantly increase the level of environmental collaboration with participating companies in upstream and downstream green supply chains and their impact on environmental work in companies in manufacturing industries in South Korea.…”
Section: Management Commitmentmentioning
confidence: 99%
“…In addition, Yusliza et al (2019) [46] found that top management commitment positively and significantly affects various green human resource management (GHRM) activities. Lee and Joo (2020) [52] show that top management is an essential factor which influences the level of collaboration between suppliers and customers in a green supply chain.…”
Section: Management Commitmentmentioning
confidence: 99%